The Implementation of Role Play to Improve EFL Speaking Skill of The Second Semester Students of IAIN KUDUS - Nikmah, Alfu (Institut Agama Islam Negeri Kudus, 2019)
Speaking is one of the important language skills. Speaking relates to daily life as communication tool. It indicates students mastering English. Unfortunately the fact has shown that the students faced many problems to improve their speaking skill because they were accustomed to use their native language in their daily life than using English. The above facts make the lecturer apply some techniques that can motivate students to speak and engage students in encouraging their speaking. One of the techniques that encourage students to speak is role play. Role play is the choice implemented by the researcher in improving the speaking skill of the first year students at IAIN Kudus since using role play, the students can express their idea, opinion, and feeling well in their performance without being worried to make mistake. Based on the result of the study, it can be concluded that the result of this research was satisfying. This research claims that it was successful in the effort in improving students’ English speaking skill through Role-Play. Role-Play activity could increase the students’ motivation in joining the teaching and learning. Their motivation was reflected in their efforts in preparing the Role-Play.